Research on Autonomous Operation Trajectory Planning of Crushers - Yan Fayi; Dong Shaojie; Lu Yu; Ni Lilu (Jixie chuandong)
The motion trajectory of the crusher working device during the working process was planned, and combined with the research theory of robot robotic arms, a crusher working device model based on the improved D-H method was established. A kinematic model was established, the forward kinematic analysis on the model was performed, and the joint angles of the rotary platform, boom, and bucket at different positions in space were obtained through inverse kinematic solutions. The motion trajectory of the working device was planned by using a fifth degree polynomial curve, a seventh degree polynomial curve, and a ninth degree polynomial curve in the joint space. On the Matlab platform, a D-H parameter model of the working device was built using the Robotics Toolbox and three methods were simulated to obtain the angle, angular velocity, and angular acceleration variation curves of the joint rotation. Comparative analysis shows that the seventh degree polynomial programming angular acceleration curve is smooth, continuous, without abrupt changes and small fluctuations, which can ensure the continuity and smoothness of the working device movement.